Assessment Methods and Techniques of the Professional Performances - HOBEANU, Loredana VĂCĂRESCU (Journal of Research in Educational Sciences; Vol 7 No 9 (2016): Journal of Research in Educational Sciences, 2016)
The professional performances assessment of the company staff is a concern of the human resources management, with the multiple implications on all the other activities of the organization, influencing in a considerable measure the organizational climate, because with the help of this there can be determined the degree to which its employees achieve their responsibilities. The need to appreciate the employees’ professional performances generated the elaboration of the multiple methods and techniques of staff appreciation and gave birth to the systems of the performances assessment. More and more organizations are currently aware that they must have implemented their own professional performances assessment system for the employees.
Keywords: assessment methods, professional performances, organization, human resources, employees.